Case Report: Diagnostic dilemma: a rare case of oesophageal hyaline vascular unicentric Castleman’s disease mimicking carcinoma - Cai, Qingqing; Zhu, Leqing; Guo, Quanwei; Kuang, Jun; Zhang, Jianhua; Tan, Jianfeng (Frontiers in Oncology, 2025)
Castleman’s disease (CD) is a rare, benign lymphoproliferative disorder of unknown aetiology. CD occurring in the oesophageal region is exceedingly rare and may be misdiagnosed as oesophageal carcinoma or lymphoma, thus posing challenges for subsequent treatment selection. A 54-year-old male with a one-month history of chest pain was admitted to our hospital. Barium oesophagography and contrast-enhanced computed tomography (CT) revealed stenosis in the lower oesophagus, accompanied by wall thickening at the gastroesophageal junction. Positron emission tomography-computed tomography (PET-CT) revealed increased glucose metabolism in the oesophageal region and lymph nodes, which was suspicious for malignancy. However, a gastroscopic biopsy revealed only inflammatory granulation tissue without evidence of malignancy. Following partial oesophagectomy with intrathoracic oesophagogastric anastomosis, pathology revealed onion-skin hyperplasia of lymphoid follicles with hyalinized vessels. Combined with immunohistochemistry, these features confirmed hyaline vascular type Castleman’s disease (HV-CD). The patient exhibited good postoperative recovery. We described a rare case of oesophageal unicentric Castleman’s disease (UCD) and highlighted the significant diagnostic challenge in distinguishing oesophageal CD from oesophageal tumours preoperatively. Furthermore, we emphasized the dual significance of complete surgical resection for UCD, achieving both a definitive diagnosis and curative treatment.